Association of 5 Well-Defined Polymorphisms in the Gene Encoding Transforming Growth Factor-β1 With Coronary Artery Disease Among Chinese Patients With Hypertension. (August 2015) - Xu, Junxia; Yu, Xiaohong; Huang, Changfu; Qin, Ruiqiang; Peng, Feng; Lin, Jinxiu; Niu, Wenquan
We assessed the association between 5 well-defined polymorphisms of the transforming growth factor-β1 (TGFB1) gene and coronary artery disease (CAD) among patients with hypertension from northeast China. All study participants were classified into patients with CAD (n = 679) and controls (n = 686) according to angiographic results. Genotyping was carried out with the ligase detection reaction method. In single-locus analysis, only genotypes of rs1800469 differed significantly between patients with CAD and controls ( P = .001); patients carrying the mutant allele of rs1800469 exhibited a 73% increased risk of CAD ( P < .001). Haplotype analysis indicated that haplotype A-T-T-C-C (alleles in the order of rs1800468, rs1800469, rs1800470, rs1800471, and rs1800472) was associated with a 1.49-fold increased risk ( P = .003). Interaction analysis identified an overall best 3-locus model including rs1800469, rs1800468, and rs1800471 ( P = .003). Taken together, we identified a synergistic interaction between TGFB1 gene multiple polymorphisms that entailed greater risk of CAD in Chinese patients.